Intra-family relations of the residents of Pertubuhan Kebajikan Warga Tua Nurul Saadah, Terengganu: guiding principles from the Qur’anic perspective - Wan Mohd Nasir , Wan Hazwani; Fatah Yasin, Raudlotul Firdaus (Universiti Teknologi Malaysia, 2016)
Elderly care centres primarily emphasize social and personal requirements of senior citizens. The number of elderly being sent to elderly care centres in Malaysia have increased due to the rapid growing of elderly population. Regrettably, a significant number of problems have been identified among the residents at these centres. Among the problems include children’s refusal to take care of their elderly pa rents because of their limited abilities, time constraint, financial and health problems, as well as sheer abandonment and negligence of responsibility by their own children and next of kin. These problems are closely related to the intra-family relationship of the residents and have been identified as one of the contributing factors of the abandonment and mistreatment of some elderly residents admitted to elderly care centres. Fundamentally, Islam stresses the rights o f parents to be treated with kindness, obedience, and honour as mentioned in the Qur’an (Al-Isra’ 23-24), and in the Hadith, the Prophet SAW reprimanded that disobedience to parents to be one of the seven major sins. With respect to this issue, this study attempts to propose Islamic guiding principles in highlighting the roles and responsibilities of children towards their parents in elderly care centres by focusing on the residents of Persatuan Kebajikan Wa rga Tua Nurul Saadah, (PKWTNS), Jerteh, Terengganu as a case study. The study will employ inductive method, observation and interviewas the main methods for completing the research.